Head home: a prospective cohort study of a nurse-led paediatric head injury clinical decision tool at a district general hospital. Issue 11 (5th August 2020) - Aldridge, Patrick; Castle, Heather; Phillips, Clare; Russell, Emma; Guerrero-Luduena, Richard; Rout, Raj
Abstract : Objectives: To assess if a nurse-led application of a paediatric head injury clinical decision tool would be safe compared with current practice. Methods: All paediatric (<17 years) patients with head injuries presenting to Frimley Park Emergency Department (ED), England from 1 May to 31 October 2018 were prospectively screened by a nurse using a mandated electronic 'Head Injury Discharge At Triage' questionnaire (HIDATq). We determined which patients underwent CT of brain and whether there was a clinically important intracranial injury or re-presentation to the ED. The negative predictive value of the screening tool was assessed. We determined what proportion of patients could have been sent home from triage using this tool. Results: Of the 1739 patients screened, 61 had CTs performed due to head injury (six abnormal) with a CT rate of 3.5% and 2% re-presentations. Of the entire cohort, 1052 screened negative. 1 CT occurred in this group showing no abnormalities. Of those screened negative, 349 (33%)/1052 had 'no other injuries' and 543 (52%)/1052 had 'abrasions or lacerations'. HIDATq's negative predictive value for CT was 99.9% (95% CI 99.4% to 99.9%) and 100% (95% CI 99.0% to 100%) for intracranial injury. The positive predictive value of the tool was low. Five patients screened negative and re-presented within 72 hours but did not require CT imaging. Conclusion: A negative HIDATq appears safe in our ED. Potentially 20% (349/1739) of all patients with head injuries presenting to our department could be discharged by nurses at triage with adequate safety netting advice. This increases to 50% (543/1739), if patients with lacerations or abrasions were given advice and discharged at triage. A large multicentre study is required to validate the tool.